The Apostasy Of George Rochberg - Gillmor, Alan (Intersections, 2009)
AbstractAn exploration of George Rochberg’s much-publicized rejection of musical modernism—in particular serialism—in the early 1960s. The paper will explore Rochberg’s conception of musical time and space, duration in music and its relationship to the roles of memory, identity, intuition, and perception in the shaping of human experience. It will explain his notion of the “metaphysical gap between human consciousness and cosmos,” which he derived in part from Wittgenstein’s proposition that ethical and aesthetic judgments lie outside the property of language. In Rochberg’s view, serialism fails to provide an organic three-dimensional model of duration as experienced through the human perception of time: past (memory) and future (anticipation) become conflated into a continuous present, and the crucial balance between information and redundancy has malfunctioned.